The Poetics of Playing - Saro, Anneli (Nordic Theatre Studies, 2014)
Despite the seemingly general agreement that we are still living in a post- or post-post-modern world andmany contemporary performancesarebased on theprinciplesof postdramatic theatre, researchers have noticed certain changes in the poetics of theatrical language, which havenot, so far, been described and analysed. Thisarticleseeksto search for a poeticsof playing?that isto say, implicit principlesof producingand perceivingcontemporary performances (non-mimetic forms of playing are beyond the scope of this investigation). These principles in themselves are not necessarily new or contemporary, although their combinations often create such an impression. The article consists of three parts. The first explores the term 'poetics' and the second the poetics of playing. The final part provides an empirical analysis of an example of the new poetics of playing. The political theatre project Unified Estonia Assembly developed the structures and strategies of politics and performing arts to their extremes, at the same time creating a powerful representation of political games. By being a kind of exceptional theatrical event, it helped to exemplify how performers can influence participants or society and how ambivalence as a strategy can be emphasized in comprehension and social interaction. Thepoeticsof playing in Unified EstoniaAssembly was based on fluid conceptions of players, roles and participants, playing and reality, and this fluidity also created astrongsenseof ambivalenceboth duringtheplayingand afterwards.